Antibacterial Activity of Etil Acetate Fraction of Chili Leaf Against Streptococcus Pyogenes and Bioautografy - Ade Irawan; Nurkhasanah Nurkhasanah; Nanik Sulistyani (Universitas Muhammadiyah Magelang, 2019)
One of the plant that has antibacterial activity is chili leaf (Capsicum frutescens L.). The purpose of this study was to determine the antibacterial activity of ethyl acetate fraction of chili leaf against Streptococcus pyogenes bacteria and conduct bioautography to see compounds that have antibacterial activity. In this study an antibacterial test for ethyl acetate fraction of chili leaf with a concentration of 5%, 10%, 20%, 40%, 80% to Streptococcus pyogenes. From the results of the inhibition zone test 5% ethyl acetate fraction produces an average inhibition zone of 6.3 mm, 10% average inhibition zone 10.3 mm, 20% average inhibition zone of 14 mm, 40% average inhibition zone 18 mm and 80% have 22.7 an average inhibition zone. In the silent phase bioautographic was used test silica gel GF 254 and for the mobile phase was used chloroform : ethyl acetate (3: 7), indicating the presence of inhibition zones on the media which had been inoculated by Streptococcus pyogenes bacteria, namely at RF 0.88. From the research that has been done, the results show that the ethyl acetate fraction of chili leaf has inhibitory zone against Streptococcus pyogenes bacteria and the spotting of compounds which have inhibitory zone has an RF of 0.88.